Shelley Duvall's Faerie tale theatre. Magical tales [videorecording (DVD)] - Duvall, Shelley, 1949-; Carradine, Robert, 1954-; Jones, James Earl; Nimoy, Leonard; Sarandon, Susan, 1946-; Kinski, Klaus; Vereen, Ben; Peters, Brock; Hines, Gregory; Redgrave, Vanessa, 1937-; McGovern, Elizabeth, 1961-; Smith, Rex (Faerie tale theatre., 2009)
"Evil magicians, cursed princes, fierce ogres, wicked queens and more fill this 4-episode collection from the award-winning series. Some of the most treasured tales of magic and enchantment are brought to life with glorious productions and magnificent costumes that will leave you spellbound... happily ever after."--container.